Tren Bunuh Diri Pada Masyarakat dan Pencegahannya Melalui Bidang Pengembangan Kehidupan Beragama (Bidang BK) - Putra, Ahmad (Institut Agama Islam Negeri Padangsidimpuan, 2024)
The author raises this issue because at the end of 2023 to the beginning of 2024 cases of suicide will once again surface, especially those that occur among people in Indonesia. Even though this case is no longer new, it is still a question mark that must be answered and resolved carefully. In this article, the author will relate and try to find views or solutions from one of the fields in counseling guidance science, namely the field of religious life development. This research uses the library research method, meaning that the author uses books, journals, research and notes which provide perfection and thoughts for this article. The important points that are the target of thought in this article include, first, discussing first what suicide is and whether suicide can be said to be a way out of every problem or even stupidity, second, the role of the Government in this suicide case, and third, views from the field of religious life development regarding suicide cases and their resolution. It is hoped that this research will become a reference and guide for future researchers to enrich their thinking in order to contribute to preventing suicide cases from occurring again.